Correlation analysis of hemoglobin, albumin, lymphocyte, platelet score and platelet to albumin ratio and prognosis in patients with lung adenosquamous carcinoma - Zhang, Tiantian; Liu, Wei; Xu, Chunhua (Frontiers in Oncology, 2023)
To investigate the effect of HALP score and PAR on prognosis of patients with ASC after surgery. A total of 52 patients diagnosed with ASC after surgical resection were collected from Nanjing Chest Hospital from 2012 to 2021. The cut-off value of △Alb, △Plt, postoperative PAR, PLR and NLR were determined by the ROC curve, the optimal cut-off value of HALP score before and after surgery was calculated by using X-tile software, and the clinicopathological characteristics were compared between the high PAR and low PAR groups and between high HALP score and low HALP score group to analyze the factors influencing the prognosis of patients with ASC. A critical value of PAR was 7.40×10^9 and an AUC of 0.737 (95%CI: 0.597-0.876, P = 0.004). The best cut-off value of the preoperative HALP score was 24.3. Univariate Cox analysis showed that the cut margin (P = 0.013), the degree of differentiation (P = 0.021), N stage (P = 0.049), △Plt (P = 0.010), △Alb (P = 0.016), PAR (P = 0.003), NLR (P = 0.025), PLR (P = 0.029), preoperative HALP score (P = 0.000) and post-operative HALP score (P = 0.010) were all associated with postoperative OS in ASC patients. Cut margin (P = 0.029), the degree of differentiation (P = 0.045), maximum tumor diameter (P = 0.018), N stage (P = 0.035), △Plt (P = 0.007), △Alb (P = 0.007), PAR (P = 0.004), NLR (P = 0.041), PLR (P = 0.030), preoperative HALP score (P = 0.000), and postoperative HALP score (P = 0.011) were related to postoperative DFS in ASC patients. Multivariate analysis revealed that PAR (HR: 6.877, 95%CI: 1.817-26.038, P = 0.005), differentiation degree (HR: 0.059, 95%CI: 0.006-0.591, P = 0.016) and preoperative HALP score (HR: 0.224, 95%CI: 0.068-0.733, P = 0.013) had significant effect on OS. Tumor maximum diameter (HR: 3.442, 95%CI:1.148-10.318, P = 0.027) and preoperative HALP score (HR: 0.268, 95%CI: 0.085-0.847, P = 0.025) had significant influence on DFS. PAR and preoperative HALP score were potentially useful biomarkers for evaluating the outcome of patients with postoperative ASC.